Measurement of productivity rate of drainage trench excavation using lean strategy - Muhammad Shahir Shaffruddeen, 1993-, author; Abdul Kadir Marsono, supervisor; Fakulti Kejuruteraan Awam (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Thesis (Sarjana Sains (Pengurusan Pembinaan)) - Universiti Teknologi Malaysia, 2018